Martyrs: Innocence, Vengeance and Despair in the Middle East by Joyce M. Davis (New York: Palgrave MacMillan, 2003. 214 pages.) (American Journal of Islam and Society, 2004)
Davis seeks to present a balanced view of terrorism vs. martyrdom, moderatevs. radical, the Muslim world vs. the West, and why 9/11 happened.The author is deputy foreign editor at Knight Ridder newspapers and is aregular contributor to her company’s 32 newspapers.In chapter 1, “A Minister’s Question,” Davis, an African-Americanpracticing Christian, wonders why African-Americans mainly have chosennon-violence, while the self-professed Muslims held responsible for 9/11chose violence. As both groups ground their struggle for justice in theirrespective religions, this gives rise to a paradox: Can God provide “superior”and “inferior” revelations? Muslims are told to “fight injustice” (e.g.,8:39, 22:39), while Christians are called upon to “turn the other cheek”(Matthew 5:39). Matthew 10:34-37, about Jesus “bringing a sword” is alsoinstructive. Moreover, if “Jesus Christ [is] the same yesterday, and today,and forever” (Hebrews 13:8) and Jesus is God, what is one to make of theOld Testament’s record of divinely sanctioned slaughter?She defines martyr according to the religion’s general view(Christianity: “generally a pacifist who suffers and dies but not kill” [p. 8];Islam: “everyone who dies in the midst of battle defending his homelandor fighting evil” [p. 9]), but does not define militant, extremist, terrorist,or moderate – a curious omission, since there are no agreed-upon meaningsfor them.Chapter 2, “The Innocents,” discusses the deaths of Palestinian andIsraeli children, how both sides exploit their martyrs (“anyone who diesin the midst of battle” [p. 27]), and mutual charges of deliberate childendangerment. She interviews parents and surviving siblings, and statesthat this has become a vicious circle of revenge, and relates the variouspsychological impacts as charges of western indifference to Palestiniandeaths, and Israel’s continued defiance of UN resolutions.Chapter 3, “The Child as Soldier-Martyr,” opens with her visit to Iran’sMartyrs Museum. She wonders if Iran might turn this “ultimate” weaponon itself as “stridently” conservative mullahs and the “freedom-hungry andangry” youths move closer to violence. After explaining Shi’ism’s originsand key events, she mentions the martyrdom of a 12-year-old boy who ...